PENGARUH PERTUMBUHAN PENJUALAN, OPERATING LEVERAGE, DAN TAX RATE TERHADAP KEBIJAKAN HUTANG DENGAN PENDEKATAN PECKING ORDER THEORY (PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2007-2010) (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This research studies the effect of growth sales, operating leverage, and tax rate on thecompany’s debt by using Pecking Order Theory approach. The research was conducted at amanufacturing company listed on the Indonesia Stock Exchange in 2007-2010. This type ofstude is a descriptive verificative. The research method used in this purposive samplingmethod. Number of sample is 40 companies observation. The hypothesis is tested by usingmultiple regression analysis. This result show that growth sales, operating leverage, and taxrate didn’t have significant influence on the company’s debt by using Pecking Order Theoryapproach at a manufacturing company on the ISE in 2007-2010. Growth sales, operatingleverage, and tax rate didn’t have significant influence with the company’s debt by usingPecking Order Theory approach.Keyword : Company’s Debt, growth sales, operating leverage, tax rate, and pecking ordertheory.